Requirement for a conserved serine in both processing and joining activities of retroviral integrase. - Katz, R A (1992)
Retroviruses encode a protein, the integrase (IN), that is required for insertion of the viral DNA into the host cell chromosome. IN alone can carry out the integration reaction in vitro. The reaction involves endonucleolytic cleavage near the 3' ends of both viral DNA strands (the processing step), followed by joining of these new viral DNA ends to host DNA (the joining step). Based on their evolutionary conservation, we have previously identified at least 11 amino acid residues of IN that may be essential for the reaction. Here we report that even conservative replacements of one of these residues, an invariant serine, produce severe reductions in both the processing and joining activities of Rous sarcoma virus IN in vitro. Replacement of the analogous serine of the type 1 human immunodeficiency virus IN had similar effects on processing activity. These results suggest that this single conserved serine is a component of the active site and that one active site is used for both processing and joining. Replacement of this serine with certain amino acids resulted in a loss or reduction in DNA binding activities, while other replacements at this position appeared to affect later steps in catalysis. All of the defective Rous sarcoma virus INs were able to compete with the wild-type protein, which supports a model in which IN functions in a multimeric complex.